Tingkat Kepatuhan Minum Obat Anti Tuberkulosis pada Pasien TB Paru Dewasa di RSU Hermina Depok Tahun 2024: Adherence to Anti-Tuberculosis Treatment Among Adult Pulmonary TB Patients at Hermina Hospital, Depok in 2024 - Tri Mitha Hardianita; Leli Nurlaeli (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2025)
Pulmonary tuberculosis remains a major public health problem in Indonesia, with a high incidence rate partly caused by poor patient adherence to anti-tuberculosis drugs (OAT). This study aimed to determine the level of medication adherence among adult outpatients with pulmonary TB at Hermina General Hospital Depok in 2024. This research employed a descriptive design with a cross-sectional approach conducted from August to October 2024. The sample consisted of 99 respondents selected using an accidental sampling technique. Data were collected using the Indonesian version of the Morisky Medication Adherence Scale (MMAS-8) questionnaire and analyzed descriptively based on frequency distribution and percentage of adherence levels. The results showed that 93% of respondents demonstrated high adherence, 7% had moderate adherence, and none showed low adherence. The high level of adherence was influenced by adequate health education, strong family support, and patients’ awareness of the importance of completing treatment. These findings also indicate the effectiveness of the Directly Observed Treatment Short-course (DOTS) program implemented in private hospitals. In conclusion, most pulmonary TB patients at Hermina General Hospital, Depok, exhibited high adherence to OAT therapy, and continuous educational interventions are recommended to maintain treatment success and prevent drug resistance.